Fast Food Consumption Habits in Students: A Correlational Study - Reny Sulistyowati; Agnes Dewi Astuti; Rikiy Rikiy; Yuyun Christyanni; Nang Randu Utama; Christine Aden; Mars Khendra Kusfriyadi; Dedi Cahyo Nusantoro; Melie Melie (GHMJ (Global Health Management Journal), 2026)
Background: Fast food consumption among high school adolescents is higher due to limited knowledge about nutritious food, so they have a positive attitude towards fast food. This makes it important to research how to reduce the craze for fast food through education for teenagers. Aims: To identify whether there is a relationship between knowledge and attitudes with fast food consumption habits in SMPN 8 Palangka Raya students. Methods: The research design used was correlation analysis with a cross-sectional approach, and the study population was all students of SMPN 8 Palangka Raya. The number of respondents was 100 students with a simple random sampling technique. The research instrument used a knowledge and attitude questionnaire, and the data that had been collected were analyzed using the chi-square test. Results:  The majority of students' knowledge in consuming fast food has good knowledge (71%) and the attitude of students in consuming fast food is mostly positive (97%). Based on Chi Square analysis, there is a no significant relationship between knowledge and attitudes about the habit of consuming fast food (ρ value > 0.05). Conclusions: The results of this study show that there is no relationship between knowledge and eating habits because knowledge is an internal factor and there are still many external factors that influence the selection of food and food consumption habits of each individual in determining and choosing food and consuming it which will shape behavior patterns and eating habits.  Future research could use a qualitative approach to further explore external factors influencing fast food consumption habits, such as peer influence, advertising, and family habits. Furthermore, intervention studies involving school-based nutrition education, media campaigns, and parental and community involvement could be conducted to evaluate the effectiveness of a multidimensional approach in changing fast food consumption habits in adolescents.